2013
DOI: 10.2478/s13382-013-0137-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect in the lungs of rats after inhalation exposure to benzalkonium chloride

Abstract: Background: Benzalkonium chloride (BAC) is a quaternary ammonium compound (QAC) toxic to microorganisms. Inhalation is one of the major possible routes of human exposure to BAC. Materials and Methods: Experiments were performed on female Wistar rats. The rats were exposed to aerosol of BAC water solution at the target concentration of 0 (control group) and 35 mg/m 3 for 5 days (6 h/day) and, after a 2-week interval, the animals were challenged (day 21 ) with BAC aerosol at the target concentration of 0 (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In alveolar and bronchial epithelial cells, BAC (1-100 µg/mL) treatment has been shown to induce acute cytotoxicity with cell membrane disruptions [14,16]. Inhalation of BAC damages airway epithelium resulting in the release of proteins and LDH to the bronchioalveolar spaces in rodents [11,12,15]. Thus, necrotic cell lysis has been considered to be the primary consequence of BAC-induced pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alveolar and bronchial epithelial cells, BAC (1-100 µg/mL) treatment has been shown to induce acute cytotoxicity with cell membrane disruptions [14,16]. Inhalation of BAC damages airway epithelium resulting in the release of proteins and LDH to the bronchioalveolar spaces in rodents [11,12,15]. Thus, necrotic cell lysis has been considered to be the primary consequence of BAC-induced pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, 17 in 28 asthmatic patients showed at least 20% decrease of 1-s forced expiratory volume (PD 20 FEV 1 ) after the inhalation of anti-asthma respirator solutions containing BAC (0.35 to 5.55 µmol) [10]. Animal studies have demonstrated that BAC inhalation induces pulmonary irritation, inflammation, and damages the blood-air barrier in rodents [11][12][13][14][15]. Several mechanisms of BAC cytotoxicity, such as cell membrane disruption, oxidative stress, and DNA damage have been proposed in in vitro studies using human lung cell lines [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…LDH and total proteins, the biomarkers of pulmonary toxicity, are leaked into bronchoalveolar space from injured bronchial/alveolar cells and damaged airway structures . It has been also shown that inhalation exposures to BAC cause significant increases of BALF protein and LDH in mice and rats . In contrast to BAC, the pulmonary toxicity of TEG is known to be very low; the LC 50 of acute TEG aerosol inhalation by rats is greater than 4400 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…BAC included in nebulized bronchodilators for treatment of asthma and chronic obstructive pulmonary diseases has been reported to cause bronchoconstriction and bronchospasm . Rodents that singly or repeatedly inhaled BAC show pulmonary irritation, inflammation, and damage to the blood‐air barrier . Moreover, BAC administered via oral and intravascular routes in rats causes pulmonary edema and interstitial pneumonia, with a higher tissue concentration of BAC in the lungs than in the blood and other organs.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation of higher concentrations of BAC induced intense pulmonary effects and inflammation. However, it may not be the cause of death because inflammatory response was not fatal in those studies [7,8].…”
Section: Introductionmentioning
confidence: 93%